Towards implementing Multicultural Education Judeo-Moroccan Cultural Heritage as a case Study - Ahmed Hamzaoui, (المجلة الإفريقية للدراسات المتقدمة في العلوم الإنسانية والاجتماعية, 2022)
Jewish identity and heritage are deeply- rooted in the Moroccan society. For centuries, the Jews have represented an important constituent of this community. Morocco was a haven for Sephardic Jews during times of Christian repression following the great waves of emigration between 1391 and 1492. Judeo-Moroccan diaspora and presence in state-and-society has been either neglected or disregarded as a field of study and, therefore, has been overlooked in the school and university syllabic reforms. Nevertheless, the 2011 Moroccan Constitution preamble displays the fabric of the diverse and renewed Moroccan heritage. As a result, The Jewish history and culture are going to be embedded in the upcoming national school curricula as a first demarcate in the Arab world to “inoculate” Moroccan youth against extremism and anti-Semitism, highlight Morocco's enriched identity, and help nurture future citizens’ consciousness of their diverse heritage. This article examines the implications of such assertive action as keystone in Judeo-Moroccan multicultural collective identity. Keywords: Judeo-Moroccan, curriculum, heritage, anti-Semitism, diversity.